Meshing methods in CFD simulations of EV battery systems - Virtanen, Emma (My University, 2024)
For a rapidly moving industry, such as automotive, computational fluid dynamics provides insight and guidance on the thermal behaviour, optimization and development of electric vehicles battery systems. In today's society, with climate change and searching for more sustainable solutions, electric vehicles (EV) have become one of the top priorities in automotive industry. CFD provides industry a swift answers in development and finding more accurate ways to conduct CFD simulations speeds up said development. Mesh creation is one of the crucial points in CFD simulation that affects greatly to accuracy and efficiency of the simulation. There are multiple ways to go about the mesh creation and software tend to have many ways to do it. This thesis will go through certain aspects of meshing in CFD, such as what are unstructured and structured meshes, the cell types themselves and meshing methods. In the experiment part of this thesis it will be studied how octree method differs from conventional type of meshing method in a CFD simulation of a small EV battery.
Keywords: CFD, Simulation, EV battery, Octree, Polyhedra, Meshing